Genetic resistance of tomato hybrids [Solanum lycopersicum L. (Mill.)] to tomato spotted wilt virus (TSWV) - Gabriel, Julio (2013)
This research was conducted at the PROINPA Foundation’s greenhouse and laboratory in Cochabamba, Bolivia in 2012. Its objective was to evaluate the resistance and susceptibility to Tomato spotted wilt virus – TSWV, Tomato cholorotic spot virus – TCSV and Groundnut ringspot virus – GRSV in 10 tomato hybrids. Phenotypic and molecular pattern (SCAR marker SW-421) evaluations were performed in order to differentiate homozygous and heterozygous resistant from susceptible plants. Results showed that molecular marker Sw421 is co-located with the TSWV-resistance Sw-5 gene. A TSWV-resistance band (R) was observed at 940 bp and showed the homozygous presence of the Sw-5 allele (Sw-5/Sw-5) in PROINPA 2 (Aguai) and PROINPA 9 (Bonita) varieties. PROINPA 1 (Andinita), PROINPA 3 (Arami), PROINPA 4 (Yara), PROINPA 5 (Pintona), PROINPA 6 (Jasuka) and PROINPA 10 (Bola Pera) varieties, showed a TSWV resistance band (H) at 900- 940 bp in the heterozygous state (Sw-5/Sw-5+). Only PROINPA 7 (Redonda), the male parent 71 LACHING 89S Sw-5 and the variety Shannon showed TSWV susceptibility gene (S) at 900 bp in the homozygous-recessive state (Sw-5+/Sw-5+). The results of the severity analysis and of DAS- ELISA were confirmed by the molecular analysis.